Nanoparticle Coalescence: Computational Modeling of Nanoparticle Coalescence (Adv. Theory Simul. 6/2019). Issue 6 (4th June 2019) - Grammatikopoulos, Panagiotis; Sowwan, Mukhles; Kioseoglou, Joseph
Abstract : In article number1900013 Panagiotis Grammatikopoulos, Mukhles Sowwan, and Joseph Kioseoglou provide a comprehensive review on the fundamental mechanisms and simulation tools of nanoparticle coalescence. Numerous case studies are presented of various materials and potential applications, including aerosol fabrication, neuromorphic computation, and nanoparticle‐support interaction as an extreme case of coalescence; also, the essence of coalescence is clarified by contrasting it to soft agglomeration.